Scalable mesoporous biochars from bagasse waste for Cu (II) removal: Process optimisation, kinetics and techno-economic analysis - Julius G. Bongosia; Amthal Al-Gailani; Ben W. Kolosz; Adrian Loy Chun Minh; Serene Sow Mun Lock; Kin Wai Cheah; Martin J. Taylor (Journal of Environmental Management, 2024)

Rethinking of the future sustainable paradigm roadmap for plastic waste management: A multi-nation scale outlook compendium - Adrian Chun Minh Loy; Juin Yau Lim; Bing Shen How; Chung Loong Yiin; Serene Sow Mun Lock; Lam Ghai Lim; Hatem Alhamzi; ChangKyoo Yoo (Science of The Total Environment, 2023)

Progress in thermochemical co-processing of biomass and sludge for sustainable energy, value-added products and circular economy - Yi Herng Chan; Serene Sow Mun Lock; Bridgid Lai Fui Chin; Mee Kee Wong; Adrian Chun Minh Loy; Shin Ying Foong; Chung Loong Yiin; Su Shiung Lam (Bioresource Technology, 2023)

Hydrogen sulfide (H2S) conversion to hydrogen (H2) and value-added chemicals: Progress, challenges and outlook - Yi Herng Chan; Adrian Chun Minh Loy; Kin Wai Cheah; Slyvester Yew Wang Chai; Lock Hei Ngu; Bing Shen How; Claudia Li; Serene Sow Mun Lock; Mee Kee Wong; Chung Loong Yiin; Bridgid Lai Fui Chin; Zhe Phak Chan; et al. (Chemical Engineering Journal, 2023)

Microwave processing of oil palm wastes for bioenergy production and circular economy: Recent advancements, challenges, and future prospects - Shin Ying Foong; Yi Herng Chan; Serene Sow Mun Lock; Bridgid Lai Fui Chin; Chung Loong Yiin; Kin Wai Cheah; Adrian Chun Minh Loy; Peter Nai Yuh Yek; William Woei Fong Chong; Su Shiung Lam (Bioresource Technology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Representation of Boundary-Layer Processes in Numerical Weather Prediction and Climate Models - John M. Edwards; Anton C. M. Beljaars; Albert A. M. Holtslag; Adrian P. Lock (Boundary-Layer Meteorology, 2020)

Optimal configuration and resolution for the first convection‐permitting ensemble of climate projections over the United Kingdom - Giorgia Fosser; Elizabeth Kendon; Steven Chan; Adrian Lock; Nigel Roberts; Mike Bush (International Journal of Climatology, 2020)
Convection‐permitting models (CPMs) provide a better representation of sub‐daily precipitation statistics and convective processes on both climate and weather forecasting timescales. This study aims to establish what horizontal resolution and physical process settings are suitable for the first ensemble of convection‐permitting climate projections for the United Kingdom. For this purpose, 12‐year‐long simulations were run using three different convection‐permitting resolutions (grid spacing of 4 km, 2.2 km and 1.5 km) each with several configurations. The focus is on the ability to represent sub‐daily precipitation due to its potential for high impacts on society through flooding. The analysis shows that the use of a finer grid spacing within the convection‐permitting regime improves the representation of sub‐daily precipitation but the added value decreases as the grid becomes increasingly finer, while the computational costs substantially increase. Changes in the representation of physical processes can have as much impact as the grid spacing and can lead to similar differences in the diurnal cycle as between convection‐parametrized models and CPMs. Although the 4km model shows some key deficiencies that make it unreliable for climate projection, the 2.2km model performs as well as the 1.5km model for most of the metrics examined with considerable benefits in terms of computer cost. The optimal configuration and resolution identified here is being used for an ensemble of simulations run within the UK Climate Projections 2018 (UKCP18) project, which allows, for the first time, an estimate of uncertainty in future changes at convection‐permitting scale and providing more reliable climate change projections at local and hourly scales.

An Observational Case Study of Persistent Fog and Comparison with an Ensemble Forecast Model - Jeremy Price; Aurore Porson; Adrian Lock (Boundary-Layer Meteorology, 2015)

The diurnal cycle of marine cloud feedback in climate models - Mark J. Webb; Adrian P. Lock; Alejandro Bodas-Salcedo; Sandrine Bony; Jason N. S. Cole; Tsuyoshi Koshiro; Hideaki Kawai; Carlo Lacagnina; Frank M. Selten; Romain Roehrig; Bjorn Stevens (Climate Dynamics, 2015)

Coupling between subtropical cloud feedback and the local hydrological cycle in a climate model - Mark. J. Webb; Adrian P. Lock (Climate Dynamics, 2013)

Radiation Fog. Part II: Large-Eddy Simulations in Very Stable Conditions - Aurore Porson; Jeremy Price; Adrian Lock; Peter Clark (Boundary-Layer Meteorology, 2011)

Combining Non-local Scalings with a TKE Closure for Mixing in Boundary-layer Clouds - Adrian Lock; Jocelyn Mailhot (Boundary-Layer Meteorology, 2006)